Tracing Treasure In Narrative: Revealing The Value Of Material Wealth In Hamka's Sabariah Novel - Putri, Karyn Eka; Nastiti, Utari; Rosa, Silvia; Anwar, Khairil (Universitas Andalas, 2025)
This research aims to analyze the values of material wealth expressed in Sabariah's novel and simultaneously reflect society's social structure and relationships. The sociological approach of literature is used to explore how the representation of material wealth in literary works functions as a mirror and shapes social structure. At the same time, it examines the relationship between material wealth and social structure in Sabariah's novels. Pierre Bourdieu's concept of economic, social, and symbolic capital is used to understand how wealth functions as a status and power-forming element in the narrative. Data collection was carried out through a text study of the novel Sabariah. The data unit is sourced from parts of the text. Data analysis was carried out thematically with a descriptive method. This study's findings show four forms of representation of material wealth in the novel Sabariah. The four forms are the exposure of the ideas and ideas of the importance of material wealth, material wealth as a symbol of power, wealth as an ambiguous social value, and material wealth/property, which can be a driver of conflict. This research concludes that the novel Sabariah turned out to be a sociocultural documentation of the Minangkabau people in his time, which was published by Hamka very critically